1969
DOI: 10.1111/j.1744-6570.1969.tb00346.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PERSONALITY OF HIGH EARNING MBA'S IN BIG BUSINESS1

Abstract: Summary AN effort was made to find personal qualifications that might be predictive of earnings in business. A follow‐up by questionnaire five years after graduation was made for members of three MBA classes who had previously taken an eleven‐instrument battery. Ninety percent responded. A comparison of the highest third and the lowest in terms of present compensation showed 13 differences at the .05 level of significance or higher among 55 predictor variables. At the .01 level were second year Graduate School… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1
1

Year Published

1975
1975
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 1 publication
3
33
1
1
Order By: Relevance
“…Figure 1 shows a link between objective and subjective career success. Based on past research which has found that objective and subjective career success are positively related (Bray & Howard, 1980;Harrell, 1969;, we believe that objective success will positively predict subjective career success. Although the causal direction of this relationship could be argued to be reciprocal, in this study we assume that objective career success predicts subjective success for several reasons.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Figure 1 shows a link between objective and subjective career success. Based on past research which has found that objective and subjective career success are positively related (Bray & Howard, 1980;Harrell, 1969;, we believe that objective success will positively predict subjective career success. Although the causal direction of this relationship could be argued to be reciprocal, in this study we assume that objective career success predicts subjective success for several reasons.…”
mentioning
confidence: 85%
“…Wolfle (1973) concluded that most studies have not adequately considered the role of motivation in predicting earnings, and Whitely et al (1991) (Cox & Cooper, 1989;Gutteridge, 1973;Harrell, 1969;Whitely et al, 1991). In the present study, we assessed not only the number of hours worked per week, but also the number of evenings worked.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, researchers have also recognized that managers' and professionals' career mobility and financial rewards are often, at least partly, allocated on the basis of informal interpersonal processes (Coates and Pellegrin 1957;Pfeffer 1977 (Dreher et al 1985;Harrell 1969;Pfeffer 1977;Weinstein and Srinivasan 1974). The exception to this observation is the study conducted by Whitely et al (1991).…”
Section: Introductionmentioning
confidence: 99%
“…Plusieurs études (Harrell, 1969 ;Pietrowski et Rock, 1963 ;Smoley et Slivinski, 1971 ;Wald et Doty, 1965) • Dominateurs, ascendants, agressifs (Livingston, Ghiselli) • Autonomes, indépendants (Haire et al)…”
Section: Les Entrepreneursunclassified